Effect of Drying Conditions on the Catalytic Performance, Structure, and Reaction Rates over the Fe-Co-Mn/MgO Catalyst for Production of Light Olefins - Majid Abdouss; Maryam Arsalanfar; Nima Mirzaei; Yahya Zamani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
The MgO-supported Fe-Co-Mn catalysts, prepared using co-precipitation procedure, were tested for production of light olefins via CO hydrogenation reaction. The effect of a range of drying conditions including drying temperature and drying time on the structure and catalytic performance of Fe-Co-Mn/MgO catalyst for Fischer-Tropsch synthesis was investigated in a fixed bed micro-reactor under the same operational conditions of T = 350 °C, P = 1 bar, H2/CO = 2/1, and GHSV = 4500 h-1. It was found that the catalyst dried at 120 °C for 16 h has shown the best catalytic performance for CO hydrogenation. Furthermore, the effect of drying conditions on different surface reaction rates was also investigated and it was found that the precursors drying conditions influenced the rates of different surface reactions. Characterization of catalyst precursors and calcined samples (fresh and used) was carried out using powder X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), Brunauer-Emmett-Teller (BET) measurements, Temperature Programmed Reduction (TPR), Thermal Gravimetric Analysis (TGA), and Differential Scanning Calorimetry (DSC). Characterization results showed that different investigated variables (drying conditions) influenced the structure, morphology and catalytic performance of the ternary catalysts.